Multi-Criteria Decision Method Applied to Path Planning for Mobile Robots - Carmo, Caio V. S. Do; Seruffo, Marcos C. R.; Oliveira, Roberto C. L. De (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2022: Anais do XIV Simpósio Brasileiro de Robótica e XIX Simpósio Latino Americano de Robótica, 2022)
This article presents a proposal for path planning of mobile robots using an approach based on the Analytic Hierarchy Process (AHP) multi-criteria decision model. Like other multi-criteria decision methods, the AHP considers and evaluates different candidates/alternatives under different criteria and defines the alternative that best satisfies the relationship between the criteria. The algorithm proposes the evaluation of alternatives based on four criteria: the distance to the target, the angle to the target, the possibility of collision with obstacles and deviation from the planned path. To this end, a global movement planning is performed and will be used by the AHP to define its point-to-point movement. To validate and perform a practical/real analysis of the proposed algorithm, simulations are performed in the CoppeliaSim environment in conjunction with Matlab, using the Pioneer 3-DX mobile robot.